Mehrsprachigkeit und Schulerfolg – die europäische (deutsche) Perspektive - Altmayer, Claus (Stellenbosch Papers in Linguistics Plus, 2012)
Multilingualism and multilingual education in Africa are different from multilingualism andmultilingual education in Europe. Nevertheless, to some extent the circumstances are comparable. Inboth regions there are currently important academic and political discussions about the significance ofthe first language in the process of second language acquisition and about the effectiveness ofbilingual education. Against this background the paper outlines the discussions in Germany about theimpact "mother tongue education" may have on the acquisition of a second language (German), on theone hand, and on the different models of bilingual education, on the other hand, especially with regardto migrant contexts. There is some research on these topics, but more empirical evidence is urgentlyneeded, in Europe as well as Africa.Keywords Schlüsselbegriffe: Mehrsprachigkeit, Migration, Muttersprache-unterricht, Herkunftssprache,bilingualer Unterricht, Interdependenzhypothese, konzeptionelle Schriftlichkeit: multiligualism, migration, mother tongue education, language of origin, bilingualeducation, interdependece hypothesis, conceptual writing